Studi Kasus Best Practice Pemungutan Cukai atas Minuman berpemanis dalam kemasan di Meksiko - Ryan Nanda Putra Dipinto; Milla Sepliana Setyowati (Politeknik Ganesha Medan, 2025)
This study examines the implementation of excise policy on Sugar-Sweetened Beverages (SSBs) in Mexico as a best practice case study for application in Indonesia. The high consumption of SSBs in Mexico has significantly contributed to the rise in obesity and non-communicable diseases, such as diabetes and heart disease. To address this issue, Mexico imposed an excise tax of 1 peso per liter on SSBs starting in 2014. This policy aims to reduce sugar consumption by increasing the price of SSBs in the market, thus discouraging excessive consumption. Based on related data and studies, the policy has proven effective in reducing SSB consumption by 6-8%, particularly in urban areas where consumption levels were highest. This research highlights Mexico's excise collection methods, including the efficient monthly reporting mechanism without the need for tax stamps, which simplifies compliance for producers and regulators alike. Additionally, it analyzes the challenges faced by Mexico, such as the necessity for stricter advertising regulations and the promotion of healthier food alternatives to further amplify the positive impact of the excise policy. Key lessons from Mexico show that excise policies on SSBs in Indonesia must be supported by comprehensive public health measures, including educational campaigns, and an integrated reporting system to ensure transparency and effectiveness. The results of this study are expected to serve as a valuable reference for policymakers in Indonesia in implementing effective and sustainable SSB excise policies that could help curb the rising health issues associated with excessive sugar consumption.